Ubezpieczenie od odpowiedzialności cywilej jako jedna z metod zarządzania przedsiębiorstwem - Jędrzychowska, Anna (Civil Liability Insurance as one of the Methods of the Company's Management, 2006)
The article concerns the third party insurance that is found in enterprises. It presents three categories of this insurance, i.e. personal, connected with production, and damages in natural environment. Among the issues discussed in the paper there are product insurances, contract insurances that indicate the company's protection from the leading staff mistakes (members of the board and managers insurance, etc.). Also the employer insurance is described, as different from other third party insurances. The article also shows which elements of a company's activity are significant for the fee calculation.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1109, s. 286-295